How to Cheat in Photoshop Elements 10 : Release Your Imagination - Asch, David and Caplin, Steve (Oxford, U.K. Elsevier, 2012)
Answers to anyone who has ever wanted to take their creative skills in Elements one stage further. Starting with the basics of layers, selections and transformations, this title helps readers in creating their own movie posters, textures and caricatures. It features sections on outputting your images for web or print.
Include Illustrations and Glossary
Keywords: Photography--Digital techniques